Implantação de Sistemas Agroflorestais na Agricultura Familiar: um caminho para a transição agroecológica - Bezerra, Leila Pires (2018)
The rural development model adopted in the last decades has had great social, economic and environmental impacts demonstrating the need to seek more sustainable ways. This study presents the research carried out in Agroforestry Systems (SAF), implemented by family farmers in Sumaré II and III settlements, and in Cooperacra, located in the municipalities of Sumaré and Americana, respectively , in the state of Sao Paulo. The first chapter refers to the analysis of the process of knowledge construction on SAFs and their contribution to the agroecological transition process. The methodology was based on the Case Study and the research instruments used were the Focus Group and the Field Diary. As results, we observe social changes in the organization of farmers and in the areas of SAF and its surroundings as well as its potential in promoting leaps in the process of agroecological transition. The second chapter presents the evaluation of the development of SAFs implemented by family farmers and discusses their influence factors. The methodology was based on participant observation and discourse analysis. As a result, we observed that the construction and appropriation of agroecological knowledge strongly influenced the development of SAFs; however, other factors, such as traditional knowledge, farmers' economic situation and land ownership and their relation to autonomy, also interfered in this process. The third chapter presents the soil quality analysis of SAFs and the comparison of these results with chemical and physical soil attributes obtained by conventional methods. The methodology used was Pfeiffer Circular Chromatography. The results demonstrated that the method can provide an overview and reliable of the state of the soil and that there was correlation with the results of the conventional methods. Considering the relevance of Agroforestry Systems in promoting the agroecological transition, it is necessary to deepen the research on this production system, in order to improve its practices, as well as to demonstrate its economic, social and environmental viability.